Effect of osseodensification on the increase in ridge thickness and the prevention of buccal peri-implant defects: an in vitro randomized split mouth pilot study - Fausto Frizzera; Rubens Spin-Neto; Victor Padilha; Nicolas Nicchio; Bruna Ghiraldini; Fábio Bezerra; Elcio Marcantonio (BMC, 2022)
Abstract Background Implant installation with conventional drilling can create buccal bone defects in areas of limited ridge thickness. Implant installation with osseodensification may aid in preventing buccal bone defects in these situations. This in vitro pilot study evaluated the impact of osseodensification on the increase in alveolar ridge thickness and the prevention of buccal peri-implant defects. Methods Ten fresh pig mandibles with limited bone thickness were selected for use in an experimental randomized split mouth pilot study. Two site-preparation protocols were used: conventional drilling with cutting burs (CTL, n = 10) and osseodensification with Densah® burs (OD, n = 10). After implant bed preparation, 20 implants (4.5 × 10 mm) were placed in the prepared sites and the insertion torque was recorded. Clinical and photographic analysis evaluated ridge thickness and the extent (height, width, and area) of bone defects in the buccal and lingual bone walls following implant placement. Three-dimensional measurements were performed using STL files to analyze the increase in buccal ridge thickness following site preparation and implant placement. The height of the buccal bone defect was considered as the primary outcome of this study. Defect width, area, implant insertion torque, and linear buccal ridge increase after implant site preparation and installation were also assessed. Non-parametric evaluations were carried out with the Mann-Whitney test to verify intergroup differences. Results There was no statistically significant difference between groups in the baseline ridge thickness. OD presented a significantly higher insertion torque, associated with reduced buccal and lingual bone defect width, in comparison to CTL. Conclusions The increase in buccal ridge thickness after site preparation and implant placement was significantly higher in OD compared to CTL. Osseodensification increased the ridge thickness through expansion and reduced buccal bone defects after implant installation.